(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Socrates being compelled to drink hemlock, and the dilemma of Antigone has underscored the problem of obligation and competing and conflicting moral values the universal of sincere citizens to disobey particular law on right a ground that it is repugnant to the moral law to which all persons ought to, and do owe allegiance. In the tradition of Socrates, Antigone and Thoreau, there emerged in India, Mohandas Karamchand Gandhi, who through his technique of Satyagraha gave mankind an extremely potent instrument for effecting fundamental change – an answer (clothed in traditional and familiar terms) to the agony of the aggrieved.Today, ahimsa and Satyagraha have become subjects of academic interest, with scholars pondering over their implications, some with serious misgivings viz-a-viz their efficacy in the face of ICBMs and Star Wars, some with fond memories of actual participation and others with cynicism. Satyagraha according to Bondurant is .... a technique more widely used than understood and one which yet called for testing in the field of social and political action. When, in 1948, Mahatma Gandhi died by an assassin’s bullet, the experiments in truth’ which he had begun, remained far from complete.”In this research paper, it has been my endeavour to analyses the Foundations of Gandhi’s Satyagraha, both in relation to contemporary political thought and Indian philosophical tradition, and examine, its relevance to the prevailing situation, showing at the same tine how Satyagraha is the culmination of what is sometimes referred to as Gandhism’. Another fact that it is hoped will emerge from this part is the role of Gandhi in using Hindu tradition, not to revive the spirit of conservatism, but transform these concepts in such a way that only the Hindu terminology remained familiar – but now symbolized a different set of values.